Synthesis and in vivo evaluation of ortho-[124I]iodohippurate for PET renography in healthy rats. (September 2016) - Pathuri, Gopal; Hedrick, Andria F.; Awasthi, Vibhudutta; Cowley, Benjamin D.; Gali, Hariprasad
Abstract: Ortho-[ 131 I]iodohippurate [ 131 I]OIH (marketed as Hippuran I 131), a gold standard for radionuclide renography, and [ 123 I]OIH were in clinical use for decades. Here we radiolabeled OIH with 124 I (a positron emitter) to combine the desirable biological properties of OIH and to enable the use of positron emission tomography (PET) for renography. [ 124 I]OIH was synthesized with a slight modification to a previously reported method for the kit preparation of [ 123 I]OIH based on the Cu(II) catalyzed isotope-exchange reaction. Our method utilized heating at 120 °C under sealed condition in a heating block instead of autoclaving. [ 124 I]OIH was obtained with a radiochemical purity of >99.3%, radiochemical yield of 94.5%, and specific activity of ~17 MBq/mg. Biodistribution studies in healthy Sprague Dawley rats revealed results comparable to that of [ 131 I]OIH as reported in the literature. The PET-derived [ 124 I]OIH renograms revealed an average time-to-peak of 2.8±0.4 min and the average time-to-half-maximal activity of 11.4±1.5 min, which are also comparable to that of [ 131 I]OIH as reported in the literature. Results from this study indicate that the synthesis of [ 124 I]OIH without using an autoclave and [ 124 I]OIH PET renography are feasible. Graphical abstract: Highlights: Radiosynthesis of [ 124 I]OIH was achieved without using an autoclave. Biodistribution of [ 124 I]OIH in healthy rats is comparable to that of [ 131 I]OIH. PET renography using [ 124 I]OIH is feasible.